4D‐Var Inversion of European NH3 Emissions Using CrIS NH3 Measurements and GEOS‐Chem Adjoint With Bi‐Directional and Uni‐Directional Flux Schemes. Issue 9 (6th May 2022) - Cao, Hansen; Henze, Daven K.; Zhu, Liye; Shephard, Mark W.; Cady‐Pereira, Karen; Dammers, Enrico; Sitwell, Michael; Heath, Nicholas; Lonsdale, Chantelle; Bash, Jesse O.; Miyazaki, Kazuyuki; Flechard, Christophe; et al.
Abstract: We conduct the first 4D‐Var inversion of NH3 accounting for NH3 bi‐directional flux, using CrIS satellite NH3 observations over Europe in 2016. We find posterior NH3 emissions peak more in springtime than prior emissions at continental to national scales, and annually they are generally smaller than the prior emissions over central Europe, but larger over most of the rest of Europe. Annual posterior anthropogenic NH3 emissions for 25 European Union members (EU25) are 25% higher than the prior emissions and very close (<2% difference) to other inventories. Our posterior annual anthropogenic emissions for EU25, the UK, the Netherlands, and Switzerland are generally 10%–20% smaller than when treating NH3 fluxes as uni‐directional emissions, while the monthly regional difference can be up to 34% (Switzerland in July). Compared to monthly mean in‐situ observations, our posterior NH3 emissions from both schemes generally improve the magnitude and seasonality of simulated surface NH3 and bulk NH x wet deposition throughout most of Europe, whereas evaluation against hourly measurements at a background site shows the bi‐directional scheme better captures observed diurnal variability of surface NH3 . This contrast highlights the need for accurately simulating diurnal variability of NH3 in assimilation of sun‐synchronous observations and also the potential value of future geostationary satellite observations. Overall, our top‐down ammonia emissions can help to examine the effectiveness of air pollution control policies to facilitate future air pollution management, as well as helping us understand the uncertainty in top‐down NH3 emissions estimates associated with treatment of NH3 surface exchange. Plain Language Summary: Atmospheric ammonia contributes to air pollutants and excessive deposition of reactive nitrogen that is detrimental to sensitive ecosystems. Ammonia is emitted mainly by agricultural livestock and fertilizer use. While surface measurements of NH3 are sparse, satellite observations can provide near daily global coverage. Here we calculate monthly NH3 emissions over Europe, the only region adopting NH3 control policies, using an air quality model coupled with a process‐based bi‐directional NH3 flux scheme and NH3 measurements observed by the CrIS satellite instrument. Our CrIS‐derived annual regional total anthropogenic NH3 emissions are close (<2% difference) to statistic‐based bottom‐up estimates and are 10%–20% lower than when treating NH3 exchange between the atmosphere and biosphere as one‐way emissions. Our top‐down NH3 emissions estimates may help to assess the efficacy of NH3 abatement policies and provide quantitative support for future policy making. Key Points: First 4D‐Var inversion to include bi‐directional flux of NH3, based on CrIS NH3 and cross‐validated with surface observations Bi‐directional flux reduces posterior regional NH3 emissions by 10%–20% annually (monthly up to 34%), compared to uni‐directional emissions Posterior NH3 emissions generally improve simulated seasonality and magnitude of NH3 and NH x wet deposition